Use of the Weibull distribution function for describing cleaning kinetics of high pressure water jets in food industry. (July 2019) - Gerhards, Christian; Schramm, Maria; Schmid, Andreas
Abstract: The Weibull distribution function can be used to describe cleaning kinetics of high pressure water jets. This function has been proposed previously to describe the soil removal of heat exchangers in milk industry during CIP processes. Weibull distribution function can be applied to model different types of kinetics by use of two parameters. Thus, characteristic cleaning times can be calculated more precisely than using an exponential function. This is necessary for proper simulation of the cleaning process of machines and equipment in food industry. Experimental trials were performed in cleaning milk protein soil from stainless steel plates with pressures from 20 to 60 bar at temperatures of 30–50 °C. In many cases, experimental data could be described equally well using an exponential function, but in specific cases, e.g. at low pressure (20 bar) or low temperature (30 °C), the Weibull distribution function resulted in much better fit. Highlights: Cleaning kinetics of high pressure water jets was studied. Weibull distribution function can be applied to model different types of cleaning kinetics by use of two parameters. Characteristic cleaning times can be calculated more precisely than using an exponential function. This is necessary for proper simulation of the cleaning process of machines and equipment in food industry.